Trả lời bởi giáo viên

Đáp án đúng: a

Đặt $t = 3x \Rightarrow dt = 3dx \Rightarrow dx = \dfrac{{dt}}{3}$, khi đó:

$\begin{array}{*{20}{l}}{\int {f\left( {3x} \right){\mkern 1mu} {\rm{d}}x} {\rm{\;}} = \dfrac{1}{3}\int {f\left( t \right)dt} {\rm{\;}} = \dfrac{1}{3}\left( {2t\ln \left( {3t - 1} \right)} \right) + C}\\{ = \dfrac{1}{3}\left( {2.3x.\ln \left( {3.3x - 1} \right)} \right) + C = 2x\ln \left( {9x - 1} \right) + C}\end{array}$

Vậy $\int {f\left( {3x} \right){\mkern 1mu} {\rm{d}}x} {\rm{\;}} = 2x\ln \left( {9x - 1} \right) + C$

Hướng dẫn giải:

Sử dụng công thức đổi biến $t = 3x$ để tính nguyên hàm $\int {f\left( {3x} \right){\mkern 1mu} {\rm{d}}x} $.

Câu hỏi khác